Tiếp cận dạy học phân hóa tiến tới cá thể hóa trong phát triển chương trình giáo dục thể chất ở trường đại học - Trần Xuân Bách, Trần Xuân Bách; Nguyễn Xuân Biên, Nguyễn Xuân Biên (Tạp chí Giáo dục, 2026)
In the context of higher education shifting strongly towards a learner-centered approach and focusing on developing lifelong physical activity skills, physical education needs to be reformed to acknowledge individual differences and create opportunities for progress for each student. This research systematizes the scientific basis of differentiated instruction towards individualization in university physical education, clarifies pedagogical principles and curricula, and proposes a framework for applying the differentiated instruction towards individualization approach in the development of physical education curricula in universities. The research results contribute to affirming the role of differentiated instruction as a curriculum management orientation, which is significant for the development and assurance of the quality of physical education programs in higher education institutions today.